Assessment of the Nutritional Status of Children Living in Orphanages in the City of Douala, Cameroon - Okalla, Cécile Ebongue; Koum, Daniele Kedy; Penda, Calixte Ida; Mefo’o, Jean-Pierre Nda; Wanye, Fanta; Eloumou, Servais Albert; Temfack, Elvis; Luma, Henry Name (International Journal of Child Health and Nutrition, 2019)
Introduction: Malnutrition is characterised by metabolic disturbances identified by measurement of anthropometric and biological parameters. The purpose of this study was to determine the nutritional profile of children living in orphanages and to investigate the factors associated with malnutrition in these institutions. Methods: A cross-sectional study was conducted on subjects aged 0 to 18, living in 13 orphanages in Douala. Socio-demographic data, anthropometric and biological parameters were collected. The diagnosis of malnutrition at the clinical level was based on Z score <-2 for the different index and >2 for Weight-for-Height and Body Mass Index for Age. A blood sample permits the photometric assay of albumin, pre-albumin, and C Reactive Protein. The results were interpreted according to reference values for age. Results: Among the 176 children included, the average age was 10±4 years with a male predominance. The majority of children (51.1%) were placed in orphanages for lack of financial resources, and one or both parents orphaned were 42.1%. The wasting, underweight and stunting rates were 5.6%, 4.7%, and 18.2%, respectively. Hypo-pre-albuminemia and hypo-albuminemia were observed in 42.6% and 34.7% of children respectively. CRP was increased in 5.1% of cases. Stunting and orphanages with one caregiver for more than 5 children were predictive factors for hypo-albuminemia and Hypo-pre-albuminemia. Conclusion: Rates of wasting, stunting and underweight were high. Several children had sub-clinical malnutrition despite normal anthropometric index. These results recall the importance of biology for screening, in order to prevent the occurrence of clinical malnutrition.